2009
DOI: 10.3109/01421590903193596
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions by medical students of their educational environment for obstetrics and gynaecology in metropolitan and rural teaching sites

Abstract: Medical students' perceptions of their learning environment in obstetrics and gynaecology were not influenced by the geographical site of delivery or their gender but were positively related to higher academic achievement. Providing appropriate academic and clinical support systems have been put in place the education of medical students can be extended outside major hospitals and into outer metropolitan and rural communities without any apparent reduction in perceptions of the quality of their learning enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 17 publications
2
24
0
5
Order By: Relevance
“…Other authors have reported exactly opposing results (Mayya & Roff 2004), i.e. female students were significantly less satisfied with the educational environment than male students in Argentina (Roff et al 1997, or no or only minor gender differences were found (Till 2005;Miles & Leinster 2007;Carmody et al 2009). Cultural differences could be playing a role here.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Other authors have reported exactly opposing results (Mayya & Roff 2004), i.e. female students were significantly less satisfied with the educational environment than male students in Argentina (Roff et al 1997, or no or only minor gender differences were found (Till 2005;Miles & Leinster 2007;Carmody et al 2009). Cultural differences could be playing a role here.…”
Section: Discussionmentioning
confidence: 71%
“…One reason for our results could be that the learning environment was on the whole rather negatively evaluated in the present sample and that the expected relationship between a good learning environment and good performance would rather develop in a positive atmosphere. Another reason could be the assessment of performance by means of objective and, above all, written theoretical measures (first state examination), for which Carmody et al (2009) had previously found no relationship with DREEM in contrast to clinical practical performance. However, this was not confirmed by other authors (Pimparyon et al 2000;Sun 2003;Mayya & Roff 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…clinical placement location or university site) (e.g. Varma et al 2005;Carmody et al 2009;McKendree 2009;Bennet et al 2010;Denz-Penhey & Murdoch 2010 …”
Section: Use Of the Dreemmentioning
confidence: 99%
“…Nossos resultados mostram que os estudantes de medicina brasileiros têm uma percepção positiva de seu ambiente educacional, medida por meio do escore total e dos escores médios de cada domínio do DREEM. A média dos escores totais foi semelhante às encontradas em outros estudos internacionais (Abraham et al, 2008;Demirören et al, 2008;Carmody et al, 2009). O ensino baseado em fatos memorizáveis segue a lógica do modelo jesuítico, utilizado no período colonial brasileiro, cuja metodologia era regulamentada por um documento denominado Ratio Studiorum, idealizado por uma comissão e jesuítas no século XVI.…”
Section: 50 (14)unclassified